Extending the Event-Based Programming Model to support Sensor-Driven Ubiquitous Computing Applications - Haahr, Mads (IEEE Computer Society, 2009)
We propose an extension to the event-based programming model for sensor-driven ubiquitous computing applications. The extension consists of three abstractions: Multi-Event Handlers, Event Streams and Execution Policies. We believe that these additional abstractions simplify the task of writing applications in this domain. In this position paper we present the extensions and demonstrate our prototype middleware implemented in C.
IEEE Middleware Support for Pervasive Computing Workshop (PerWare 2009)
Keywords: Ubiquitous computing; Prototypes; Writing; Educational institutions; Computer science; Scalability; Application software; Filters; Middleware; Peer to peer computing; Smart & Sustainable Planet